Pengaruh Efektivitas Iklan Sandal Terapi Terhadap Keputusan Pembelian Pada Konsumen Kayen Store The Influence of The Effectiveness of Therapy Sandals Advertising on Purchasing Decisions for Kayen Store Consumers - Mutiara, Mutiara; Arum, Khorifah; Melati, Sunti (EBBANK, 2024)
Therapeutic sandals are a health product from Kayen Store which has been marketed using advertising via facebook ads since March 2022. With the increasing number of consumers buying therapeutic sandals, Kayen Store always uses advertising as its marketing strategy, which means that advertising is still considered capable of attracting consumer purchasing decisions. This research aims to determine the effect of the effctiveness of therapeutic sandals advertising on purchasing decisions for Kayen Store consumers. This research uses quantitative methods with the EPIC Model method to measure advertising effectiveness. The EPIC Model includes empathy, persuasion, impact, and communication. Where data collecting was carried out by distributing questionnaires, so that the data obtained could then be analyzed more deeply regarding the influence of the effectiveness of therapeutic sandal advertising on purchasing decisions for Kayen Store consumers. The results of the analysis based on the EPIC Model show that advertising fot therapeutic sandals is considered effective in introducing its products to Kayen Store consumers. The results of simultaneous hypothesis testing show that the variables of empathy, persuasion, impact, and communication have a significant effect on purchasing decisions for Kayen Store consumers. Then the results of partial hypothesis testing show that only the impact variable has a significant effect on the purchasing decision of Kayen Store consumers. Meanwhile, the variables of empathy, persuasion, and communication partially have an insignificant effect on purchasing decisions for Kayen Store consumers.